Labor Indicators and Manufacturing Companies Ownership Patterns in Russia and its Regions: Results of Quantitative Analysis; Oeconomia Copernicana; Vol. 9, No. 2 - Spitsin V. V. Vladislav Vladimirovich; Mikhalchuk A. A. Aleksandr Alexandrovich; Pavlova I. A. Irina Anatolievna; Spitsina (Spitsyna) L. Yu. Lubov Yurievna (2018, 2018)
Title screen